Islam and Artificial Intelligence (AI): Ethical Considerations and the Potential Impact on Islamic Societies - mudrik mudrik; Almujahid Almujahid; Cittra Juniarni (Islamic Studies Journal (ISLAM), 2024)
This research discusses the challenges and opportunities faced by the Muslim community in applying artificial intelligence (AI) in the field of education, especially in the context of teaching Islamic values. Using a systematic literature review approach, this research identifies various barriers related to technological infrastructure, accessibility, and ethical considerations that arise from the use of AI. On the other hand, this research also highlights the potential of AI to improve the effectiveness of teaching and learning, and provides examples of successful implementation in various countries. The research results show that collaboration between stakeholders, including educational institutions, ulama, and government, is very important to overcome existing challenges. Policy recommendations and strategies for AI integration in line with Islamic values ​​are also presented. It is hoped that this research can make a significant contribution in understanding the application of AI in Islamic education and pave the way for further research in this area.